2016
DOI: 10.1103/physrevlett.117.167204
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Spin Hall Angles by Alloying

Abstract: Within a combined experimental and theoretical study it is shown that the spin Hall angle of a substitutional alloy system can be continuously varied via its composition. For the alloy system Au_{x}Pt_{1-x} a substantial increase of the maximum spin Hall angle compared to the pure alloy partners could be achieved this way. The experimental findings for the longitudinal charge conductivity σ, the transverse spin Hall conductivity σ_{SH}, and the spin Hall angle α_{SH} could be confirmed by calculations based on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

15
82
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 44 publications
15
82
0
Order By: Relevance
“…See Supplementary Materials [37] for more information on the samples and experimental methods. grown Pt/FM samples are comparable to those reported from damping measurements on similar structures in the literature [9,11,13,16,24,38]. However, all of these values of eff,α ↑↓ are markedly larger than the expected value eff ↑↓ =0.31×10 15 Ω -1 m -2 as calculated with Eq.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…See Supplementary Materials [37] for more information on the samples and experimental methods. grown Pt/FM samples are comparable to those reported from damping measurements on similar structures in the literature [9,11,13,16,24,38]. However, all of these values of eff,α ↑↓ are markedly larger than the expected value eff ↑↓ =0.31×10 15 Ω -1 m -2 as calculated with Eq.…”
supporting
confidence: 88%
“…Interfacial spin transport is at the root of many spintronic phenomena, e.g. spin-orbit torques (SOTs) [1,2], spin magnetoresistance (SMR) [3,4], the spin Seebeck effect (SSE) [5][6][7], and spin pumping [8][9][10][11][12][13][14][15][16] in heavy-metal /ferromagnet (HM/FM) systems. The key factor determining the spin transmission and spin backflow (SBF) of a HM/FM interface [17,18] is the effective spin-mixing conductance [19] eff ↑↓ = HM/FM ↑↓ /(1+2 HM/FM ↑↓ /GHM) (1) where HM/FM ↑↓ is the bare interfacial spin-mixing conductance, GHM = 1/λsρxx, ρxx, and λs are the spin conductance, the resistivity, and the spin diffusion length of the HM layer, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The intrinsic mechanism from Berry curvature in the conduction band gives the same dependence ρ xy ∝ ρ 2 xx as the side-jump contribution so that, for example the SHE of AuPt (SHA=0.3 at max.) alloys could be explained by a predominant intrinsic effect rather than ascribed to sidejump [16].In this letter we present a study of Au-based alloys with W and T a impurities. We demonstrate that the side-jump scattering mechanism dominates in AuTa alloys, and generates high spin Hall angles (up to + 0.5) with the additional advantage of resistivities (ρ AuT a < 85µΩ.cm) smaller than in most materials with SHA in the same range.…”
mentioning
confidence: 99%
“…Among all HMs, 5d transition metals such as Pt [14], β-Ta [5], and β-W [15] shown that 5d HM-related alloys and oxides can generate sizable SHE and even possess greater spin Hall ratios than pure HMs. For instance, Hf(Al)-doped Pt [16], Au-doped Pt [17], PtMn [18], W-doped Au [19], and WOx [20] all show larger spin Hall ratios or DL  while compare to their pure HM counterparts. Even by oxidizing or doping dopants into light transition metals such as Cu, the spin Hall ratio can be significantly enhanced [21,22].…”
mentioning
confidence: 99%